Five decades of teacher burnout research (1970–2024): A comprehensive bibliometric analysis - Jie Yao; Melissa Ng Lee Yen Abdullah (Acta Psychologica, 2025)
Over the past five decades, research on teacher burnout has expanded significantly, emphasizing its profound impact on educators' well-being, job performance, retention, and overall educational quality. However, the vast body of literature makes it difficult to synthesize the field's evolution, leading scholars to call for more structured overviews. To address this gap, this study conducts a bibliometric analysis to examine prominent authors, their collaborative networks, international collaboration patterns, thematic influences, and their role in shaping the development and impact of teacher burnout research. Using the Social Sciences Citation Index (SSCI) in Web of Science (WOS), this study analyzes publications on teacher burnout from 1970 to 2024. Findings shows that a significant surge in research began in 2012 (24 publications) and the upward trend continued steadily. The leading authors in teacher burnout research represent a geographically diverse group, yet the lack of strong global collaboration highlights the need for greater international partnerships, which could significantly enhance knowledge-sharing and advance research on a global scale. The findings are based on a bibliometric analysis employing keyword co-occurrence and thematic clustering techniques. The results revealed that existing studies primarily focus on key themes such as stress, self-efficacy, social support and job satisfaction within the literature on teacher occupational burnout, while critical aspects such as classroom environment, emotional intelligence and work-family conflict remain underexplored. These factors play a crucial role in burnout, as classroom conditions, emotional regulation, and work-life balance directly impact teachers' stress levels and well-being. Addressing these gaps through a more comprehensive research approach could lead to targeted and effective interventions that enhance teacher well-being, emphasizing the need for international collaboration and culturally responsive practices across diverse contexts.